Antibodies Against the Plasmodium vivax Apical Membrane Antigen 1 From the Belem Strain Share Common Epitopes Among Other Worldwide Variants - França, Ana Caroline Barbosa; Françoso, Kátia Sanches; Marques, Rodolfo Ferreira; Trossini, Gustavo H. G.; Gomes, Renan A.; Póvoa, Marinete M.; Cunha, Maristela G.; Silveira, Eduardo L. V.; Soares, Irene S. (Frontiers in Cellular and Infection Microbiology, 2021)
Malaria is a human parasitic disease distributed in many tropical countries and caused by various Plasmodium species. Plasmodium vivax has the largest geographical distribution of the Plasmodium species and is predominant in the Americas, including Brazil. Only a small number of P. vivax vaccine formulations have successfully reached clinical trials relative to their P. falciparum counterparts. One of the candidate antigens for a blood-stage P. vivax vaccine is apical membrane antigen 1 (PvAMA-1). Due to the worldwide distribution of Plasmodium parasites, a high degree of variability has been detected in this antigen sequence, representing a considerable challenge to the development of a universal vaccine against malaria. In this study, we evaluated how PvAMA-1 polymorphisms influence vaccine-derived immune responses in P. vivax malaria. To this end, we expressed 9 recombinant protein representatives of different PvAMA-1 allelic variants in the yeast Pichia pastoris: Belem, Chesson I, Sal-1, Indonesia XIX, SK0814, TC103, PNG_05_ESP, PNG_62_MU, and PNG_68_MAS. After protein expression and purification, we evaluated the breadth of the immune responses derived from malaria-exposed individuals from the Amazon region. From 611 serum samples of malaria-exposed individuals, 53.68% of them reacted against the PvAMA-1 Belem through ELISA. Positive samples were further tested against recombinant proteins representing the other PvAMA-1 allelic variants. Whereas Sal-1, Chesson I and SK0814 variants were highly recognized by tested serum samples, Indonesia XIX, TC103, PNG_05_ESP, PNG_62_MU, and PNG_68_MAS were only slightly recognized. Moreover, polyclonal sera derived from C57BL/6 mice immunized with the PvAMA-1 Belem protein predominantly recognized Belem, Sal-1, Chesson I, SK0814, and Indonesia XIX through ELISA. Last, ELISA-based competition assays demonstrated that a previous interaction between anti-Belem polyclonal serum and Sal-1, Chesson I, SK0814, or Indonesia XIX proteins could further inhibit antibody binding to the Belem variant. Our human and mouse data suggest the presence of common epitopes or cross-reactivity between Belem, Sal-1, Chesson I, and SK0814 variants. Although the PvAMA-1 Belem variant induces strain-transcendent antibodies, PvAMA-1 variants from Thailand and Papua New Guinea may need to be included in a universal vaccine formulation to achieve protection against P. vivax malaria.